Heat Stress in Broiler Chickens and the Effect of Dietary Polyphenols, with Special Reference to Willow (Salix spp.) Bark Supplements-A Review - Mihaela Saracila; Tatiana Dumitra Panaite; Camelia Puia Papuc; Rodica Diana Criste (MDPI AG, 2021)
Over the last decade, there has been a growing interest in the use of a wide range of phytoadditives to counteract the harmful effects of heat stress in poultry. Willow (Salix spp.) is a tree with a long history. Among various forms, willow bark is an important natural source of salicin, β-O-glucoside of saligenin, but also of polyphenols (flavonoids and condensed tannins) with antioxidant, antimicrobial, and anti-inflammatory activity. In light of this, the current review presents some literature data aiming to: (1) describe the relationship between heat stress and oxidative stress in broilers, (2) present or summarize literature data on the chemical composition of Salix species, (3) summarize the mechanisms of action of willow bark in heat-stressed broilers, and (4) present different biological effects of the extract of Salix species in different experimental models.